Unraveling Plant Responses to Bacterial Pathogens through Proteomics. (3rd November 2011) - Zimaro, Tamara; Gottig, Natalia; Garavaglia, Betiana S.; Gehring, Chris; Ottado, Jorgelina
Abstract : Plant pathogenic bacteria cause diseases in important crops and seriously and negatively impact agricultural production. Therefore, an understanding of the mechanisms by which plants resist bacterial infection at the stage of the basal immune response or mount a successful specific R-dependent defense response is crucial since a better understanding of the biochemical and cellular mechanisms underlying these interactions will enable molecular and transgenic approaches to crops with increased biotic resistance. In recent years, proteomics has been used to gain in-depth understanding of many aspects of the host defense against pathogens and has allowed monitoring differences in abundance of proteins as well as posttranscriptional and posttranslational processes, protein activation/inactivation, and turnover. Proteomics also offers a window to study protein trafficking and routes of communication between organelles. Here, we summarize and discuss current progress in proteomics of the basal and specific host defense responses elicited by bacterial pathogens.